1999
DOI: 10.1017/s0890037x00041919
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Clomazone Use in Rice (Oryza Sativa)

Abstract: Clomazone was applied preplant incorporated, preemergence, delayed preemergence, or postemergence and compared to pendimethalin, quinclorac, and thiobencarb for control of barnyardgrass in rice. Seven days after the clomazone postemergence application, all clomazone treatments except those applied postemergence controlled barnyardgrass ≥ 86%. At 49 d after the postemergence application, control of barnyardgrass with 0.56 and 0.67 kg/ha clomazone postemergence improved to 92 and 93%, respectively. Clomazone and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 9 publications
2
34
0
Order By: Relevance
“…Furthermore, higher rates also reduced seed head emergence and grain yield; drill-seeded production was more impacted than water-seeded (Bollich et al 2000). Webster et al (1999) observed injury to rice 7d after emergence; however less injury was produced by post-emergence treatments.…”
Section: Plant Effectsmentioning
confidence: 90%
“…Furthermore, higher rates also reduced seed head emergence and grain yield; drill-seeded production was more impacted than water-seeded (Bollich et al 2000). Webster et al (1999) observed injury to rice 7d after emergence; however less injury was produced by post-emergence treatments.…”
Section: Plant Effectsmentioning
confidence: 90%
“…Among these herbicides, clomazone (carotenoid inhibitor) stands out as the herbicide more commonly used in the preemergence of the culture and is commercially available in two formulations (Emulsifiable Concentrate -EC and Encapsulated or Microencapsulated Suspension -ES), and the ES clomazone formulation was developed recently to minimize losses by volatilization, photodecomposition (photolysis), besides providing a slower release of the molecule into the environment and, as a consequence, maximizing the residual effect on the soils on the weeds seed bank (Webster et al, 1999;Bollich et al, 2000). Therefore, there are few studies on the differences of selectivity of the clomazone formulations in the different cycles of cassava growth.…”
Section: Introductionmentioning
confidence: 99%
“…Clomazone is used as a global rice herbicide for weed control, but it could be effective against weedy rice only at high dosages (Fig. A).…”
Section: Discussionmentioning
confidence: 99%